2019
DOI: 10.3390/app9173499
|View full text |Cite
|
Sign up to set email alerts
|

Random Laser Action in Dye-Doped Polymer Media with Inhomogeneously Distributed Particles and Gain

Abstract: The properties of random lasing are investigated for bubble-structure (BS) dye-doped polymer random media in which non-scattering and no-gain regions are distributed. Experimental results demonstrate that, for BS random media, spectral narrowing and a decrease in the number of spectral spikes occur for incoherent and coherent random lasing, respectively, resulting in an increase in the spectral peak intensity in both cases. These features were observed owing to the differences in the diffusion properties of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…RL emission performance of HNT1 and HNT2 is expected to be identical because of their similar linear optical properties around ∼600 nm. Anyway, inhomogeneity in the distribution of the scatterer may lead to a slight improvement in the P in Th , as we have observed for HNT1-RhB.…”
Section: Resultssupporting
confidence: 52%
“…RL emission performance of HNT1 and HNT2 is expected to be identical because of their similar linear optical properties around ∼600 nm. Anyway, inhomogeneity in the distribution of the scatterer may lead to a slight improvement in the P in Th , as we have observed for HNT1-RhB.…”
Section: Resultssupporting
confidence: 52%
“…Spacer particles (non-scattering regions) dispersed in random gain media increase the spectral peak intensity for both coherent and incoherent random lasing [11]. This peak enhancement occurs even when the spacer particles have no gain [12].…”
Section: Design Of Random Structurementioning
confidence: 99%
“…When a laser beam is focused into a particulate medium, scatterers near the focused spot are pulled into the beam waist region, forming a non-uniform distribution of scatterers 4,5 . Earlier studies demonstrated that spacer particles (non-scattering regions) dispersed in a random gain medium increase the peak intensity of the emission spectrum 6,7 . In this study, we realize another inhomogeneous scatterer distribution, that is, localized high-density scatterer regions and low-density surrounding regions, by optical trapping.…”
Section: Introductionmentioning
confidence: 99%